Funciones como instructor de créditos grupales en la institución "Compartamos Financiera" agencia de Trujillo periodo 2014-2017 - Siccha Cabrera, Lady Erika (2017)
The present work entitled: "FUNCTIONS AS INSTRUCTOR OF GROUP CREDITS IN THE INSTITUTION" COMPARTAMOS FINANCIERA "AGENCY OF TRUJILLO PERIOD 2014 - 2017", describes the activities carried out in the work experience. The background and general data of the Company and its economic environment are detailed. Presents the theoretical framework of work performance in addition to identifying the main problems of the work and proposals made. A case presented in the Group Credit Agency is described during the work experience that allows to reinforce the methodology through a practical case. A Hypothetical - Deductive study was carried out to demonstrate the hypothesis and achieve one of the objectives through academic and work experience; applying a linear econometric model whose results indicate that the main determinants of the group credits of "Compartamos Financiera" Agency Trujillo during the period from 2014 to June 2017 are: Peru's inflation and the delinquency ratio with negative impact; while the nro. of trained personnel and the nro. of clients influence positively. These variables included in the estimated group credit model explain 98.8%. A critical evaluation of professional training was developed and proposals are presented to improve the curriculum of the Professional School of Economics. At the end, conclusions and recommendations of professional proficiency work are presented.